2018
DOI: 10.18632/oncotarget.25615
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of trophoblast cell-surface antigen 2 (TROP-2) as a novel cancer target

Abstract: TROP-2 is a glycoprotein first described as a surface marker of trophoblast cells, but subsequently shown to be increased in many solid cancers, with lower expression in certain normal tissues. It regulates cancer growth, invasion and spread by several signaling pathways, and has a role in stem cell biology and other diseases. This review summarizes TROP-2's properties, especially in cancer, and particularly its role as a target for antibody-drug conjugates (ADC) or immunotherapy. When the irinotecan metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
198
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(207 citation statements)
references
References 134 publications
2
198
1
6
Order By: Relevance
“…Tumor-associated calcium signal transducer 2 (Tacstd2, Trop2, TROP2) is a cell surface glycoprotein that has emerged as a promising therapeutic target due to its overexpression in multiple epithelial cancers (10,11). Sacituzumab govitecan (IMMU-132), an anti-Trop2 antibody conjugated with SN-38, a cytotoxic agent that targets DNA replication, has shown therapeutic activity in several malignances, including triple negative breast cancer, advanced non-small cell lung cancer, and metastatic platinum-resistant urothelial carcinoma (10,(12)(13)(14).…”
mentioning
confidence: 99%
“…Tumor-associated calcium signal transducer 2 (Tacstd2, Trop2, TROP2) is a cell surface glycoprotein that has emerged as a promising therapeutic target due to its overexpression in multiple epithelial cancers (10,11). Sacituzumab govitecan (IMMU-132), an anti-Trop2 antibody conjugated with SN-38, a cytotoxic agent that targets DNA replication, has shown therapeutic activity in several malignances, including triple negative breast cancer, advanced non-small cell lung cancer, and metastatic platinum-resistant urothelial carcinoma (10,(12)(13)(14).…”
mentioning
confidence: 99%
“…Trop-2 was first described forty years ago, however, its expression, role, and function became of great interest only few years later, after the discovery of Trop-2 overexpression on the surface of many different types of epithelial tumors [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that Trop-2 is able to promote cell proliferation by inhibiting apoptosis and accelerating cell cycle progression through increased expression of antiapoptotic genes such as BCL-2 [31]. CS are rare but highly aggressive gynecologic cancers composed of both an epithelial and sarcomatous component.…”
Section: Discussionmentioning
confidence: 99%
“…The TACSTD2 gene on chromosome 1p32, encodes the human trophoblast cell surface antigen 2 (Trop-2), a 46 kDa transmembrane glycoprotein. Many epithelial human tumors differentially express Trop-2 (8). While the functions of this protein in human tumors is not completely understood.…”
mentioning
confidence: 99%
“…Sacituzumab govitecan or IMMU-132 (SG) is a novel ADC combining the humanized RS7 antibody targeting Trop-2 coupled to a hydrolyzable linker that allows for a time dependent release of the payload to deliver SN-38, the active metabolite of irinotecan (7-ethyl-10-hydroxycamptothecin) to tumor tissue. SN-38 is significantly more potent than irinotecan (100-to 1,000fold) and SG antibody is conjugated to the toxic payload with a high ratio (8:1) without affecting targeting and pharmacokinetics (8,11,12). The hydrolysable pH-sensitive cleavable linker of SG may not only target Trop-2 when is highly overexpressed in human tumors but also induce a strong bystander effect against Trop-2 negative tumor cells (13).…”
mentioning
confidence: 99%